Social Media Adoption and SMEs Business Performance: Examining Entrepreneurship Orientation and Government Support Policies in Central Java - Novandari, Weni; Gunawan, Diah Setyorini; Bawono, Icuk Rangga; Naufalin, Rifda; Maryani, Sri; Jajang, Jajang; Sulasih, Sulasih (Journal The Winners, 2023)
The research analyzed the influence of social media adoption on SMEs’ business performance by examining the mediating role of entrepreneurship orientation and the moderating role of government support policies. The utilization of technology in business, including the adoption of social media, was significant in enhancing business performance. Previous research has shown that the adoption of social media by SMEs is a common phenomenon. However, limited SMEs have experienced a positive impact on their business performance despite adopting social media into their business operations. The research subjects consisted of 134 SMEs in Central Java that have integrated social media into their business operations. The respondents were selected using convenience sampling, and the SEM PLS method was employed as the analytical tool. This research succeeded in providing answers to the research gap, where entrepreneurship orientation mediated partially the effect of social media adoption on SMEs’ business performance. The result shows that government support policies do not moderate the effect of entrepreneurship orientation on business performance but have a direct positive effect on improving business performance. Theoretical and practical contributions are also made to the field of research concerning the interconnection of technology and marketing strategies.